A new estimation of HD/2H2 at high redshift using the spectrum of the quasar J 2123-0050. (November 2015) - Klimenko, V V; Balashev, S A; Ivanchik, A V; Varshalovich, D A
Abstract: We present a new analysis of the quasar spectrum J 2123-0050 obtained using VLT/UVES. The H2/HD absorption system at z = 2.059 was analysed. This system consists of two subsystems with z A = 2.05933 and zB = 2.05955. The HD lines have been detected only in subsystem A with the column density of log N = 13.87 ± 0.06. We have determined the column density of H2 in this subsystem, log N = 17.93 ± 0.01, which is about three times larger than estimation derived early from analyses of quasar spectrum obtained using KECK/HIRES [1]. The derived ratio HD/2H2 = (4.28 ± 0.60) × 10 -5 is the largest in quasar spectra, nevertheless it coincides with the primordial deuterium abundance within 2σ error. Additionally, we have found some evidence in the partial covering effect for the H2 system.